Ormianie Mohylowa Podolskiego w świetle materiałów V rewizji 1795 roku - Maksym Potapenko (Ksiegarnia Akademicka Publishing, 2019)
Armenians from Mohylów Podolski in the Light of the Documents from the Fifth Revision of 1795